2021
DOI: 10.3390/curroncol28010061
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Field of Pediatric Exercise Oncology: Research and Innovation Needs

Abstract: The field of pediatric exercise oncology explores the relationships between physical activity (PA), including exercise, and a range of outcomes among children and adolescents affected by cancer. Although PA is safe and beneficial for this population, several important gaps in knowledge and practice remain. In this article, we describe research and innovation needs that were developed with a team of international experts and relevant literature, a series of online surveys, and an in-person meeting. Addressing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The objectives of this meeting were to discuss the results from the information gathered in Phase I (February 2019–August 2019) and to draft the iPOEG guideline and recommendation statements. Also, attendees reviewed and commented on the literature synthesis to identify research and innovation needs in the field (see [ 44 ] for a manuscript detailing these needs).…”
Section: Methodsmentioning
confidence: 99%
“…The objectives of this meeting were to discuss the results from the information gathered in Phase I (February 2019–August 2019) and to draft the iPOEG guideline and recommendation statements. Also, attendees reviewed and commented on the literature synthesis to identify research and innovation needs in the field (see [ 44 ] for a manuscript detailing these needs).…”
Section: Methodsmentioning
confidence: 99%
“…In Germany, the interdisciplinary Network ActiveOncoKids (NAOK) is working on the expansion and implementation of exercise programs, individualized exercise counseling, qualification of pediatric oncology exercise professionals, and research projects. The evaluation of risks and benefits of exercise programs in children, adolescents, and young adults during and after cancer treatment is one of those research topics identified as relevant in the field of pediatric exercise oncology ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to regular PA, patients feel reduced tiredness, enhanced immunity, and better sleep and overall quality of life. Positive effects of PA in the field of paediatric oncology have been supported by other studies too ( 8 – 11 ). The importance of physical activity in this target group is also emphasised by the international expert group that has developed the International Paediatric Oncology Exercise Guidelines (iPOEG).…”
Section: Introductionmentioning
confidence: 52%